Synthesis, Characterization and X-Ray Crystal Structure of Copper Complex with 18-Crown-6 - Hussain, Imdad; Gillani, Rubina; McKee, Vickie; Hussain, Habib; Ali, Zulfiqar (Asian Journal of Chemistry, 2014)
A 1:1 crystal of 18-crown-6 with copper has been obtained by stirring and refluxing equimolar quantities of methanolic solution of 18-crown-6 and Cu(NO3)2 overnight. Cu-18-crown-6 complex is a crystalline solid of blue colour. The complex crystallizes in the monoclinic space group P 2 1/n, with unit cell parameters a = 10.0228(7) Å, b = 12.9341(9) Å, c = 16.7351(12)Å, a = 90.00, b = 92.089(1), g = 90.00, Z = 4, V = 2168.0 (3) Å3. Copper metal does not fit into the cavity of 18-crown-6, because the cavity size of the 18-crown-6 is bigger than the size of the copper atom. So copper metal is coordinated by water molecule and that water molecules are further connected with 18-crown-6 through hydrogenbonding between water coordinated with copper metal and oxygen atoms of the crown ether. The complex was characterized by using single crystal X-ray spectroscopy, TGA, UV-spectroscopy, IR-spectroscopy and atomic absorption spectroscopy.